BIOLOGICAL CHARACTERISTIC OF INDONESIAN GAYO HORSE - Juli Melia; Amrozi Amrozi; Muhammad Agil; Iman Supriatna (SEAMEO BIOTROP, 2022)
This study aims to find out the characteristic of gayo horse and to identify the population of gayo horse. Data collection was conducted through selection process over 100 local horse distributed in Central Aceh Sub-districts, Gayo Lues and Bener Meriah. The result was 30 gayo horses with varying age distribution. Detail observation was performed on six gayo horses of male (n=3) and female (n=3). The observation consisted of morphological observation and morphometry. Data collection of gayo horse population was based on annual report from local Animal Husbandry and Fishery Official over the last 5 years. Result showed that gayo horse has straight cranial shape similar to thoroughbred with smaller size, thick and stiff mane, and ears akin to donkey. Gayo horse body height ranges between 113-120 with body weight ranging around 215-280 kg. Gayo horse is agile despite living in mountain and able to carry heavy weight. There has been drastic decline of population in year 2010-2014. In conclusion, gayo horse is included as large pony category, and without any rescue effort, gayo horse is predicted to be extinct in 2037.